Investigating the Moderating Role of Culture on the Relationship Between Appraisals and Symptoms of Posttraumatic Stress Disorder. (September 2019) - Bernardi, Jessica; Jobson, Laura
Appraisals play a central role in posttraumatic stress disorder (PTSD). Accumulating cross-cultural psychology research has demonstrated that culture affects the way in which individuals appraise an experience. However, there is little empirical work considering the influence of culture on appraisals in PTSD. In this study, we investigated the influence of culture on trauma-related appraisals and PTSD symptoms, with a particular focus on appraisals related to control. Trauma-related appraisals and PTSD symptoms were assessed in European Australian ( n = 71) and Asian Australian ( n = 73) adult trauma survivors. The group (European Australian vs. Asian Australian) was found to moderate the relationship between control, responsibility, and agency-focused appraisals (mental defeat, mastery, present control, and self-blame) and PTSD symptoms. Findings suggest that the relationship between these appraisal types and PTSD is influenced by the extent to which an individual emphasizes the independent self-construal. The cross-sectional design prevents causal inferences being drawn from the findings. Implications for culturally informed PTSD models and treatments are discussed.